1997
DOI: 10.1016/s0022-5347(01)65178-4
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Quantitative Estimation of Infravesical Obstruction Using Ultrasonic Measurement of Bladder Weight

Abstract: Ultrasound estimated bladder weight can be measured noninvasively at the bedside and it is promising as a reliable predictor of infravesical obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Interest has therefore arisen in the development of noninvasive methods for assessing lower urinary tract function. The diagnostic potential of measurements of BWT, detrusor wall thickness, and US-estimated bladder weight in men with LUTS and various degrees of BOO have been explored [5,11-14]. …”
Section: Discussionmentioning
confidence: 99%
“…Interest has therefore arisen in the development of noninvasive methods for assessing lower urinary tract function. The diagnostic potential of measurements of BWT, detrusor wall thickness, and US-estimated bladder weight in men with LUTS and various degrees of BOO have been explored [5,11-14]. …”
Section: Discussionmentioning
confidence: 99%
“…The concept of bladder weight (BW) as a measure of bladder wall hypertrophy has also been introduced [85]. Comparison of UEBW and PFS revealed that UEBW could identify BOO with a diagnostic accuracy of 86.2% using a cutoff value of 35 g [86]. Measurement of BWT or DWT and UEBW may be a feasible option for diagnosing BOO in men with LUTS.…”
Section: Bladder/detrusor Wall Thickness and Us-estimated Bladder Weimentioning
confidence: 99%
“…[4] Obviously, for patients of any age, a reconstructive procedure is always indicated whenever overall renal function is compromised because of involvement in a solitary kidney or bilateral disease. [5] UPJO may not become apparent until middle age or later. [6] However, the majority of affected patients can in fact benefit from reconstructive intervention.…”
Section: Introductionmentioning
confidence: 99%